Migrationsberättelser i samspel - Wolanik Boström, Katarzyna (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2014)
This article takes an interview with two Polish specialist physicians, a married couple currently living and working in Sweden, as a point of departure for exploration of a co-narration of experiences of migration and hybridisation. A narrative support is offered both within the couple and by the researcher and the evaluation of a story is often strengthened by a shared laughter. The analysis focuses how ”narrative sparkles” are evoked by the decision to leave Poland, the feeling of linguistic and cultural hybridisation, the predicaments of marking status in the right way and the ambivalence of belonging to both a highly respected social stratum and the category of ”immigrants”.